Topological analysis using the Finite Element Method of the chassis of a competition motorcycle - Remache, Álvaro; Leguísamo, Julio; Tamayo, Edwin (Enfoque UTE, 2019)
This model presents a technical application of topological optimization, applied through the study of the behavior of the frame of a brand competition motorcycle, Honda CRF 230 model, with the aim of reducing the weight of the original component without altering its mechanical properties, and obtain a higher performance of the engine, greater maneuverability for the pilot and the reduction of manufacturing costs. This method of analysis is used to obtain the percentages of the chemical elements of a piece by the intensity of the light emitted by a spark, thereby acquiring the mechanical properties of the material. By means of the results, they are analyzed in different points of stress concentration of the frame; the conditions of the border are set to establish the simulation in the CAD model, and the application of the optimization of the structure through the use of the MEF method. Finally, the reduction of 67.6 % of the weight of the original chassis was included, with a safety factor of 1.41.